A legislação urbana e a ocupação de Belo Horizonte de 1897 a 2010: conjunto urbanístico da Praça da Liberdade - Ana Maria Nagem Frade (2011)
More than 80% of the worlds population live in cities, so these nucleuses need to be projected and their growth need to be planned, monitored and controlled. In the present work, the specific legislation for land use, which dictates the urban occupation dynamic and transform the landscapes, was studied. Compilation and analysis were made of Laws, Decrees and Statements which constitute the group of city construction tools and establish specific urbanistic parameters to the city of Belo Horizonte. These urbanistic plans influence the city spaces and constantly transform them. The legislation applied to the city orientates the use and occupation of the urban space public or private , outline the urban landscape, make it change or remain the same throughout time, and also transforms society. The intention was to verify changes occurred in the landscape of the Liberty Square political and administrative center from where come deliberations for the people of Minas Gerais , since the city implementation in 1897 until 2010, in order to point out the relevance of the legislation about occupation and configuration of the urban landscape and about the city spaces quality, public and private. The choice to pick that place is reinforced by the political, administrative, economical, cultural and heritage relevance of the Liberty Square, as well as for being an urban space carrying symbolism which perpetuates the identification of the people with one place. To fulfill the investigation objectives, the urban legislation of Belo Horizonte was analyzed, mainly the Land Use and Occupation Laws and the Edification Code in order to verify what happened with the Liberty Square occupation and landscape back when political and economical forces influenced it.